Differences in Adaptive and Maladaptive Coping Strategies Between Adolescents with and Without a History of Self-Harm at SMAN 1 and SMAN 2 Bangkinang Kota, Kampar Regency - Alini Alini; Faridah Mohd Said; Nia Aprilla; Bri Nofrika (PT. Anagata Sembagi Education, 2026)
Adolescent self-harm is a mental health problem associated with ineffective stress management. This study aimed to determine differences in adaptive and maladaptive coping strategies between adolescents with and without a history of self-harm at SMAN 1 and SMAN 2 Bangkinang Kota, Kampar Regency. A comparative analytic cross-sectional design was used involving 248 respondents, consisting of 124 adolescents with a history of self-harm and 124 without such history, selected using purposive sampling. Coping strategies were measured using the Brief COPE questionnaire and grouped into adaptive and maladaptive coping. The results showed that the adaptive coping score was 36.2 ± 7.8 in the self-harm group and 37.1 ± 7.2 in the non-self-harm group, with p = 0.182. Maladaptive coping scores were 22.9 ± 6.1 and 18.4 ± 5.3, respectively, with p < 0.001. In conclusion, there was a significant difference in maladaptive coping, but not in adaptive coping. These findings highlight the importance of school-based nursing interventions to reduce maladaptive coping among adolescents at risk of self-harm.